Talent Management Practices and Employee Performance: A Bibliometric Approach - Purnandika, Rona; Fazri, Daffa (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to be able to analyze talent management practices that can improve employee performance. This bibliometric analysis method is used to measure, analyze, and understand patterns in scientific literature and scientific publications related to talent management and employee performance. Through a search using the Publish or Perish tool, 82 articles were selected according to the research needs, starting from 2019 to 2023. The results of this study provide results that talent management can affect employee performance. Practices in talent management that can be applied to improve employee performance as well as important contributions to the understanding of the topic of talent management and employee performance base on existing scientific literature. This research pioneers the analysis of talent management practices aimed at improving employee performance, utilizing a bibliometric approach to uncover patterns in the scientific literature. By carefully selecting and evaluating 82 articles from 2019 to 2023 through the Publish or Perish tool, this research highlights the impactful relationship between talent management and employee performance. These findings not only underscore the applicability of talent management practices for performance improvement but also contribute significantly to the existing scientific literature, offering a new perspective on the complex relationship between talent management and employee performance.